SOCIO-ECONOMIC DEVELOPMENT AS OBJECT OF HUMAN GEOGRAPHICAL RESEARCH - Телебєнєва, Євгенія; Барило, Ірина (Human Geography Journal, 2016)
This article deals with definition of the «social and economic development» concept of by various authors. From the standpoint of social geography it was identified the main components of the socio-economic development, the key of which is the «territory», «population», «socio-geographic process». A proper interpretation of «regional socio-economic development» and block diagram of socio-geographical study of regional socio-economic development was present in this paper. The problems of comprehensive model of socio-economic development from the perspective interdisciplinary approach was defined.